1 chair is 79.99
40% discount
79.99 ÷ 100 =0.7999
0.7999 × 60 = 47.994
47.994 rounded down is $47.99
79.99-47.99=30.00
he saved $30
No,because 9 feet is way bigger than 1 foot.
Answer:
(a)![x_1=-2,x_2=1](https://tex.z-dn.net/?f=x_1%3D-2%2Cx_2%3D1)
(b)![x_1=\frac{3}{4} ,x_2=-\frac{1}{2} ,x_3=\frac{1}{4}](https://tex.z-dn.net/?f=x_1%3D%5Cfrac%7B3%7D%7B4%7D%20%2Cx_2%3D-%5Cfrac%7B1%7D%7B2%7D%20%2Cx_3%3D%5Cfrac%7B1%7D%7B4%7D)
Step-by-step explanation:
(a) For using Cramer's rule you need to find matrix
and the matrix
for each variable. The matrix
is formed with the coefficients of the variables in the system. The first step is to accommodate the equations, one under the other, to get
more easily.
![2x_1+5x_2=1\\x_1+4x_2=2](https://tex.z-dn.net/?f=2x_1%2B5x_2%3D1%5C%5Cx_1%2B4x_2%3D2)
![\therefore A=\left[\begin{array}{cc}2&5\\1&4\end{array}\right]](https://tex.z-dn.net/?f=%5Ctherefore%20A%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D2%265%5C%5C1%264%5Cend%7Barray%7D%5Cright%5D)
To get
, replace in the matrix A the 1st column with the results of the equations:
![B_1=\left[\begin{array}{cc}1&5\\2&4\end{array}\right]](https://tex.z-dn.net/?f=B_1%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%265%5C%5C2%264%5Cend%7Barray%7D%5Cright%5D)
To get
, replace in the matrix A the 2nd column with the results of the equations:
![B_2=\left[\begin{array}{cc}2&1\\1&2\end{array}\right]](https://tex.z-dn.net/?f=B_2%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D2%261%5C%5C1%262%5Cend%7Barray%7D%5Cright%5D)
Apply the rule to solve
:
![x_1=\frac{det\left(\begin{array}{cc}1&5\\2&4\end{array}\right)}{det\left(\begin{array}{cc}2&5\\1&4\end{array}\right)} =\frac{(1)(4)-(2)(5)}{(2)(4)-(1)(5)} =\frac{4-10}{8-5}=\frac{-6}{3}=-2\\x_1=-2](https://tex.z-dn.net/?f=x_1%3D%5Cfrac%7Bdet%5Cleft%28%5Cbegin%7Barray%7D%7Bcc%7D1%265%5C%5C2%264%5Cend%7Barray%7D%5Cright%29%7D%7Bdet%5Cleft%28%5Cbegin%7Barray%7D%7Bcc%7D2%265%5C%5C1%264%5Cend%7Barray%7D%5Cright%29%7D%20%3D%5Cfrac%7B%281%29%284%29-%282%29%285%29%7D%7B%282%29%284%29-%281%29%285%29%7D%20%3D%5Cfrac%7B4-10%7D%7B8-5%7D%3D%5Cfrac%7B-6%7D%7B3%7D%3D-2%5C%5Cx_1%3D-2)
In the case of B2, the determinant is going to be zero. Instead of using the rule, substitute the values of the variable
in one of the equations and solve for
:
![2x_1+5x_2=1\\2(-2)+5x_2=1\\-4+5x_2=1\\5x_2=1+4\\ 5x_2=5\\x_2=1](https://tex.z-dn.net/?f=2x_1%2B5x_2%3D1%5C%5C2%28-2%29%2B5x_2%3D1%5C%5C-4%2B5x_2%3D1%5C%5C5x_2%3D1%2B4%5C%5C%205x_2%3D5%5C%5Cx_2%3D1)
(b) In this system, follow the same steps,ust remember
is formed by replacing the 3rd column of A with the results of the equations:
![2x_1+x_2 =1\\x_1+2x_2+x_3=0\\x_2+2x_3=0](https://tex.z-dn.net/?f=2x_1%2Bx_2%20%3D1%5C%5Cx_1%2B2x_2%2Bx_3%3D0%5C%5Cx_2%2B2x_3%3D0)
![\therefore A=\left[\begin{array}{ccc}2&1&0\\1&2&1\\0&1&2\end{array}\right]](https://tex.z-dn.net/?f=%5Ctherefore%20A%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D2%261%260%5C%5C1%262%261%5C%5C0%261%262%5Cend%7Barray%7D%5Cright%5D)
![B_1=\left[\begin{array}{ccc}1&1&0\\0&2&1\\0&1&2\end{array}\right]](https://tex.z-dn.net/?f=B_1%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%261%260%5C%5C0%262%261%5C%5C0%261%262%5Cend%7Barray%7D%5Cright%5D)
![B_2=\left[\begin{array}{ccc}2&1&0\\1&0&1\\0&0&2\end{array}\right]](https://tex.z-dn.net/?f=B_2%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D2%261%260%5C%5C1%260%261%5C%5C0%260%262%5Cend%7Barray%7D%5Cright%5D)
![B_3=\left[\begin{array}{ccc}2&1&1\\1&2&0\\0&1&0\end{array}\right]](https://tex.z-dn.net/?f=B_3%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D2%261%261%5C%5C1%262%260%5C%5C0%261%260%5Cend%7Barray%7D%5Cright%5D)
![x_1=\frac{det\left(\begin{array}{ccc}1&1&0\\0&2&1\\0&1&2\end{array}\right)}{det\left(\begin{array}{ccc}2&1&0\\1&2&1\\0&1&2\end{array}\right)} =\frac{1(2)(2)+(0)(1)(0)+(0)(1)(1)-(1)(1)(1)-(0)(1)(2)-(0)(2)(0)}{(2)(2)(2)+(1)(1)(0)+(0)(1)(1)-(2)(1)(1)-(1)(1)(2)-(0)(2)(0)}\\ x_1=\frac{4+0+0-1-0-0}{8+0+0-2-2-0} =\frac{3}{4} \\x_1=\frac{3}{4}](https://tex.z-dn.net/?f=x_1%3D%5Cfrac%7Bdet%5Cleft%28%5Cbegin%7Barray%7D%7Bccc%7D1%261%260%5C%5C0%262%261%5C%5C0%261%262%5Cend%7Barray%7D%5Cright%29%7D%7Bdet%5Cleft%28%5Cbegin%7Barray%7D%7Bccc%7D2%261%260%5C%5C1%262%261%5C%5C0%261%262%5Cend%7Barray%7D%5Cright%29%7D%20%3D%5Cfrac%7B1%282%29%282%29%2B%280%29%281%29%280%29%2B%280%29%281%29%281%29-%281%29%281%29%281%29-%280%29%281%29%282%29-%280%29%282%29%280%29%7D%7B%282%29%282%29%282%29%2B%281%29%281%29%280%29%2B%280%29%281%29%281%29-%282%29%281%29%281%29-%281%29%281%29%282%29-%280%29%282%29%280%29%7D%5C%5C%20x_1%3D%5Cfrac%7B4%2B0%2B0-1-0-0%7D%7B8%2B0%2B0-2-2-0%7D%20%3D%5Cfrac%7B3%7D%7B4%7D%20%5C%5Cx_1%3D%5Cfrac%7B3%7D%7B4%7D)
![x_2=\frac{det\left(\begin{array}{ccc}2&1&0\\1&0&1\\0&0&2\end{array}\right)}{det\left(\begin{array}{ccc}2&1&0\\1&2&1\\0&1&2\end{array}\right)} =\frac{(2)(0)(2)+(1)(0)(0)+(0)(1)(1)-(2)(0)(1)-(1)(1)(2)-(0)(0)(0)}{4} \\x_2=\frac{0+0+0-0-2-0}{4}=\frac{-2}{4}=-\frac{1}{2}\\x_2=-\frac{1}{2}](https://tex.z-dn.net/?f=x_2%3D%5Cfrac%7Bdet%5Cleft%28%5Cbegin%7Barray%7D%7Bccc%7D2%261%260%5C%5C1%260%261%5C%5C0%260%262%5Cend%7Barray%7D%5Cright%29%7D%7Bdet%5Cleft%28%5Cbegin%7Barray%7D%7Bccc%7D2%261%260%5C%5C1%262%261%5C%5C0%261%262%5Cend%7Barray%7D%5Cright%29%7D%20%3D%5Cfrac%7B%282%29%280%29%282%29%2B%281%29%280%29%280%29%2B%280%29%281%29%281%29-%282%29%280%29%281%29-%281%29%281%29%282%29-%280%29%280%29%280%29%7D%7B4%7D%20%5C%5Cx_2%3D%5Cfrac%7B0%2B0%2B0-0-2-0%7D%7B4%7D%3D%5Cfrac%7B-2%7D%7B4%7D%3D-%5Cfrac%7B1%7D%7B2%7D%5C%5Cx_2%3D-%5Cfrac%7B1%7D%7B2%7D)
![x_3=\frac{det\left(\begin{array}{ccc}2&1&1\\1&2&0\\0&1&0\end{array}\right)}{det\left(\begin{array}{ccc}2&1&0\\1&2&1\\0&1&2\end{array}\right)}=\frac{(2)(2)(0)+(1)(1)(1)+(0)(1)(0)-(2)(1)(0)-(1)(1)(0)-(0)(2)(1)}{4} \\x_3=\frac{0+1+0-0-0-0}{4}=\frac{1}{4}\\x_3=\frac{1}{4}](https://tex.z-dn.net/?f=x_3%3D%5Cfrac%7Bdet%5Cleft%28%5Cbegin%7Barray%7D%7Bccc%7D2%261%261%5C%5C1%262%260%5C%5C0%261%260%5Cend%7Barray%7D%5Cright%29%7D%7Bdet%5Cleft%28%5Cbegin%7Barray%7D%7Bccc%7D2%261%260%5C%5C1%262%261%5C%5C0%261%262%5Cend%7Barray%7D%5Cright%29%7D%3D%5Cfrac%7B%282%29%282%29%280%29%2B%281%29%281%29%281%29%2B%280%29%281%29%280%29-%282%29%281%29%280%29-%281%29%281%29%280%29-%280%29%282%29%281%29%7D%7B4%7D%20%5C%5Cx_3%3D%5Cfrac%7B0%2B1%2B0-0-0-0%7D%7B4%7D%3D%5Cfrac%7B1%7D%7B4%7D%5C%5Cx_3%3D%5Cfrac%7B1%7D%7B4%7D)
Answer:
A
Step-by-step explanation:
Just put x = 80 and y = 210 into the equation...
or put x = 40, y = 90.
A:
210 - 90 = 3(80-40)
120 = 120√
B:
210 + 90 = 3(80+40)
300 = 360×
C:
210 - 90 = 2.6(80-40)
120 = 104×
D:
210 + 90 = 2.6(80+40)
300 = 312×
The first term is 2 and the common ratio = -8/2 = -4
S7 = 2 * (-4)^7 - 1
------------- = 6554 answer
-4-1